Gaṇamādhyame Bāṃlādeśera muktiyuddha = Media and the liberation war of Bangladesh. - Mamoon, Muntassir, 1951- (Centre for Bnagladesh Studies, 2002)
Articles, reports, and cartoons collected from various newspapers and news magazines on the 1971 liberation war of Bangladesh.